Unprecedentedly rapid rotational braking of the He-strong CP star HD 37776 - Mikulasek, Z.; Krticka, J.; Henry, G.W.; Zverko, J.; Ziznovský, J.; Janik, J.; Graf, T. (Известия Крымской астрофизической обсерватории, 2008)
We study long-term light variations in the well-known He-strong CP star HD 37776 = V901 Ori to search for changes in its photometric period. We analyze all published reliable photometric observations of this star, including 861uvbyβ, BV, V and Hp measurements. These observations are supplemented by 506 new BV observations obtained during the last two observing seasons. All the observations are treated simultaneously in our analysis. We confirm a previously suspected lengthening of the photometric period in HD 37776 and measure the rate of increase to be 52.4 ± 2.1 s per century (!). We interpret this ongoing period increase to be the slowing of the star's surface rotation, most likely due to momentum loss through a magnetically confined stellar wind.